Temas transversais, oficinas pedagógicas e aprendizagem significativa: uma triangulação necessária no ensino de Ciências - Silva, Wenderson Cruz da (2015)
This study aimed to discuss the pedagogical relationship and the dynamics in the triad: teacher - student - knowledge, with the reasons the Transversal Themes, the Pedagogical Workshops and Meaningful Learning in the 9th year of elementary school at Lila Maia School in the city of Parintins. The theoretical approach has its foundations in Candau (1999) which emphasizes the dynamic character of educational workshops, emphasizing that these allow the creation of various situations such as teacher training, the production of educational resources as well as the inclusion of events; Ausubel (1978,1980,2002) and Moreira (2006) have postulated that learning occur in the daily lives of all people and that this process is present in the experiences and experiences of individuals, the end, when students come to room class, they bring with them a set of attitudes that express their thoughts and concepts arising from experienced opportunities in different social groups and Brazil (1997) which classifies the Transversal Themes in 09 areas of knowledge and at the national level these are known as Parameters National Curriculum and should as its name indicates is used across, that is, applied as per the existing need in the classroom context, hence its interdisciplinary character. For the purpose could be achieved became involved in the qualitative approach to the techniques of direct observation, application of pre and post-tests and instrumentalization of 03 educational workshops on drugs and STDs to students of 9th grade of elementary school, questionnaire and structured interview with the teacher who teaches the natural sciences discipline. Also made use of field diary to record the perceptions of the researcher during the collection of data in the search location. The resulting data were from the specific core categories, and analyzed, with the theoretical contribution to Bardin Analysis (1977) from specific objectives sure that the educational workshops based in the meaningful learning provide behavioral changes in 9th graders the above school. The survey results show that in fact the work with educational workshops provide behavioral changes that in turn reflects in the learning process of students, that is, in how these are to design and internalize new content in their cognitive structures.